ANALISIS PENILAIAN TINGKAT KESEHATAN KOPERASI SIMPAN PINJAM DI KOTA MAKASSAR DITINJAU DARI NON PERFORMING LOAN (NPL) PADA TAHUN 2020-2021 : STUDI KASUS PADA KOPERASI SIMPAN PINJAM BERKAT BULUKUMBA CABANG ANTANG - UTAMI RESKY ARSYAD; TUTI SUPATMININGSIH; NURDIANA; NURJANNAH; MUHAMMAD HASAN (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
This study aims to examine how the health level of savings and loan cooperatives in Makassar City in terms of Non-Performing Loans (NPL) for the 2020 and 2021 fiscal years (Case Study on KSP Berkat Bulukumba Antang Branch). Evaluative descriptive methodology was used for this research. Sources for collecting data include books, journals, and interviews. In this study, the object that was evaluated was the level of cooperative health. The criteria used in this assessment are the provisions issued by Bank Indonesia. From the results of the analysis, it can be concluded that based on the results of the analysis, it was found that the Non-Performing Loan credit at the Berkat Bulukumba Cooperative Antang Branch in 2020-2021 was 31.5%, in accordance with Bank Indonesia Regulation Number 17/11/PBI/2015, then it can be concluded that the level of credit risk is in the unhealthy category.